Impacts of drought and elevated temperature on the seeds of malting barley - Nagel, Manuela; Arc, Erwann; Rajjou, Loïc; Cueff, Gwendal; Bailly, Marlene; Clément, Gilles; Sanchez-Vicente, Inmaculada; Bailly, Christophe; Seal, Charlotte E.; Roach, Thomas; Rolletschek, Hardy; Lorenzo, Oscar; et al. (Frontiers in Plant Science, 2022)
High seed quality is key to agricultural production, which is increasingly affected by climate change. We studied the effects of drought and elevated temperature during seed production on key seed quality traits of two genotypes of malting barley (Hordeum sativum L.). Plants of a “Hana-type” landrace (B1) were taller, flowered earlier and produced heavier, larger and more vigorous seeds that resisted ageing longer compared to a semi-dwarf breeding line (B2). Accordingly, a NAC domain-containing transcription factor (TF) associated with rapid response to environmental stimuli, and the TF ABI5, a key regulator of seed dormancy and vigour, were more abundant in B1 seeds. Drought significantly reduced seed yield in both genotypes, and elevated temperature reduced seed size. Genotype B2 showed partial thermodormancy that was alleviated by drought and elevated temperature. Metabolite profiling revealed clear differences between the embryos of B1 and B2. Drought, but not elevated temperature, affected the metabolism of amino acids, organic acids, osmolytes and nitrogen assimilation, in the seeds of both genotypes. Our study may support future breeding efforts to produce new lodging and drought resistant malting barleys without trade-offs that can occur in semi-dwarf varieties such as lower stress resistance and higher dormancy.